2007
DOI: 10.1177/0022343307080856
|View full text |Cite
|
Sign up to set email alerts
|

Public Attitudes Towards Peace: The Greek-Cypriot Position

Abstract: In 1974, Turkey divided Cyprus by military force into the north and south, giving the Turkish Cypriots full control of the north. Since then, the United Nations (UN) has attempted to resolve the Cyprus problem, but diplomatic efforts have always fallen short. In 2004, UN Secretary-General Kofi Annan proposed a plan that would reunify Cyprus. In a public referendum that followed, about two-thirds of Turkish Cypriots voted for the plan; however, three-quarters of Greek Cypriots rejected the plan. To help illumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Generations of Cypriots have now grown up on a divided island and know no other reality. Perhaps for this reason, survey research has persistently demonstrated that attitudes toward reconciliation are less favorable among the young than among the old in the Greek Cypriot community in Cyprus (''Solving the Cyprus Problem, 2011Problem, , 2013Georgiades, 2007;Sitas et al, 2007;Yucel and Psaltis, 2020). Second, the type of contact that Cypriots engage in upon crossing tends to be shallow and transactional.…”
Section: Intergroup Contact In Cyprusmentioning
confidence: 99%
“…Generations of Cypriots have now grown up on a divided island and know no other reality. Perhaps for this reason, survey research has persistently demonstrated that attitudes toward reconciliation are less favorable among the young than among the old in the Greek Cypriot community in Cyprus (''Solving the Cyprus Problem, 2011Problem, , 2013Georgiades, 2007;Sitas et al, 2007;Yucel and Psaltis, 2020). Second, the type of contact that Cypriots engage in upon crossing tends to be shallow and transactional.…”
Section: Intergroup Contact In Cyprusmentioning
confidence: 99%
“…Th e Turkish Cypriot nationalist position can be juxtaposed with the Greek Cypriot nationalist position to demonstrate how views become entrenched, reinforced, and intractable (Stavrinides 1976). Research has also been done on the attitudes regarding the possibility of peace (Georgiades 2007); ethnocentrism is found to inhibit the peace process in spite of the fact that Greek Cypriots generally do not mistrust Turkish Cypriots.…”
Section: Why Cyprus?mentioning
confidence: 99%
“…Culturally speaking, because of frequent marketing research, the Cyprus public is much more accustomed to participating in brief phone research than face to face interviews or mailed surveys. Moreover, previous studies have repeatedly shown that telephone survey research is an effective way of assessing public opinion and sensitive experiences in Cyprus (Georgiades, 2003(Georgiades, , 2006(Georgiades, , 2007(Georgiades, , 2008Georgiades and Potocky-Tripodi, 2000). Interview data were handwritten verbatim by the researcher.…”
Section: Data Collection Proceduresmentioning
confidence: 99%